KATA KERJA BANTU UTAMA DALAM NOVEL EMMA VOLUME III KARYA JANE AUSTEN - Tamangendar, Trinisela; Pelealu, Hetty; Manus, Jeane A. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSRACT Auxiliary verb is also called as ?helping verb?. In English language there are two types of auxiliary verbs those are Primary auxiliary verbs and Modal auxiliary verbs. This research is entitled: ?Primary Auxiliary Verbs on The Novel Emma Volume III by Jane Austen? as the requirement to accomplish the Bachelor?s Degree in the Faculty of Humanities of English major, Sam Ratulangi University. This research aims to identify forms, classify criteria, and analyze the function of primary auxiliary verb in the novel Emma volume III by Jane Austen. The Writer used concept from Muir that discusses are be, have, do as the primary auxiliary verbs and they had four main criteria include negation, inversion, substitution and marked positive. The Writer also used concept from Quirk et all that discusses two functions of primary auxiliary verb are function as a main verb and function as an auxiliary. The result of this study The Writer have found 16 forms of primary auxiliary verbs those are 8 forms of be (am, is, are, was, were, be, been, being), 3 forms of have (have, had, has), and 5 forms of do (do, did, does, doing, and done) with 4 main criteria include negation, inversion, substitution, and marked positive. The Writer also found 2 function of primary auxiliary verb those are function as a copula and as an auxiliary. Keywords: primary auxiliary verb, syntax, novel ?Emma?